2009
DOI: 10.1128/jvi.01008-09
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of Hepatitis C Virus Strain JFH1 Polymerase

Abstract: The hepatitis C virus (HCV) isolate JFH1 represents the only cloned wild-type sequence capable of efficient replication in cell culture, as well as in chimpanzees. Previous reports have pointed to the viral polymerase NS5B as a major determinant for efficient replication of this isolate. To understand the underlying mechanisms, we expressed and purified NS5B of JFH1 and of the closely related isolate J6, which replicates below the limit of detection in cell culture. The JFH1 enzyme exhibited a 5-to 10-fold-hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
91
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 52 publications
7
91
0
1
Order By: Relevance
“…Murayama et al took advantage of the properties of these isolates, generating chimeric replicons and demonstrating that the NS3 helicase-coding region, NS5B, and the 3ЈNTR were the major elements for efficient JFH1 replication, in which NS5B was the most important single determinant (32). In a subsequent study we found that the JFH1 polymerase indeed exhibited a 5-to 10-fold-higher specific activity in vitro than the J6 enzyme, consistent with the polymerase activity itself contributing to efficient replication of JFH1 (41). This was due to significantly more efficient de novo RNA synthesis of JFH1 than of J6 NS5B.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Murayama et al took advantage of the properties of these isolates, generating chimeric replicons and demonstrating that the NS3 helicase-coding region, NS5B, and the 3ЈNTR were the major elements for efficient JFH1 replication, in which NS5B was the most important single determinant (32). In a subsequent study we found that the JFH1 polymerase indeed exhibited a 5-to 10-fold-higher specific activity in vitro than the J6 enzyme, consistent with the polymerase activity itself contributing to efficient replication of JFH1 (41). This was due to significantly more efficient de novo RNA synthesis of JFH1 than of J6 NS5B.…”
mentioning
confidence: 67%
“…Differences in main-chain conformation between pairs of molecules were objectively assessed using the program ESCET (39). As in our previous work (20,41), we used significance values (ESCET "lolim" parameter) of 5.0 sigmas to identify broader conformational differences and 2.5 sigmas to take into account all significant conformational differences. When comparing the two high-resolution structures reported here, we also used a lolim value of 2.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in enzyme kinetics between the wild-type and phosphomimetic RdRp suggest that the phosphorylation of Thr33 may modulate the function of the polymerase. In HCV, it has been shown that disruptions to the interactions between the finger and thumb domains lead to a reduction in de novo RdRp activity whereas efficient primer extension activity is maintained (9,10,24). Since NoV utilizes both de novo and proteinprimed RNA synthesis, it is possible that phosphorylation of NoV RdRp could alter the balance between these modes of RNA synthesis.…”
mentioning
confidence: 99%